EMPATHIC-N in a Greek-Cypriot sample: confirming its factorial structure - Elena Papamichael; Myria Ioannou; Michael A. Talias (BMC, 2018)
Abstract Background Family-centered care has been receiving increased attention during the last decades and health professionals recognize family satisfaction with care as an important health indicator. The Empowerment of Parents in The Intensive Care-Neonatology (EMPATHIC-N) is a newly developed, yet empirically reliable and valid measure for the assessment of parental satisfaction with the care provided by Neonatal Intensive Care Units (NICU). The present study aims to present the Greek version of the EMPATHIC-N and to confirm its factorial structure. Methods The EMPATHIC-N was translated in Greek using a forward-backward translation and was piloted before use. A sample of 256 families receiving intensive care at the NICU of Archbishop Makarios III Public Hospital in Cyprus which is the only NICU in Cyprus, participated in the validation study of the EMPATHIC-N. Confirmatory factor analyses were performed using SPSS and AMOS 24.0. Results The Greek version of the EMPATHIC-N had good psychometric characteristics (Cronbach's alpha = .87). The CFAs for the separate subscales of professionalism, organization, information, parental involvement and intervention for the EMPATHIC-N showed that all five subscales represented five distinct components of parental satisfaction with care. The CFA of the general instrument supported that a second-order model with a higher-order factor reflecting the organizational structure (professionalism, intervention and organization loaded on this factor) fitted the data best [χ2 (259) = 405.332, p < .001, ΤLI = .887, CFI = .903, RMSEA = .065 (90% CI .058, .073), SRMR = .0597]. Conclusions EMPATHIC-N is a valid and reliable measure for the assessment of parental satisfaction with neonatal care in a Greek-Cypriot context. The organizational dimension of the NICUs is an important component with specific research and clinical implications for the enhancement of parental satisfaction with care.